The impact of analgesic on EMG and other biosignals in a postoperative setting - Gruss, Sascha; Schmid, Matthias; Walter, Steffen; Schick, Benedikt; Holler, Lena; Barth, Eberhard (Frontiers in Medicine, 2023)
Background In the clinical context, the assessment of pain in patients with inadequate communication skills is standardly performed externally by trained medical staff. Automated pain recognition (APR) could make a significant contribution here. Hereby, pain responses are captured using mainly video cams and biosignal sensors. Primary, the automated monitoring of pain during the onset of analgesic sedation has the highest relevance in intensive care medicine. In this context, facial electromyography (EMG) represents an alternative to recording facial expressions via video in terms of data security. In the present study, specific physiological signals were analyzed to determine, whether a distinction can be made between pre-and post-analgesic administration in a postoperative setting. Explicitly, the significance of the facial EMG regarding the operationalization of the effect of analgesia was tested. Methods N = 38 patients scheduled for surgical intervention where prospectively recruited. After the procedure the patients were transferred to intermediate care. Biosignals were recorded and all doses of analgesic sedations were carefully documented until they were transferred back to the general ward. Results Almost every biosignal feature is able to distinguish significantly between ‘before’ and ‘after’ pain medication. We found the highest effect sizes (r = 0.56) for the facial EMG. Conclusion The results of the present study, findings from research based on the BioVid and X-ITE pain datasets, staff and patient acceptance indicate that it would now be appropriate to develop an APR prototype.